2020
DOI: 10.1136/annrheumdis-2019-216713
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin limits osteoarthritis development and progression through activation of AMPK signalling

Abstract: ObjectivesIn this study, we aim to determine the effect of metformin on osteoarthritis (OA) development and progression.MethodsDestabilisation of the medial meniscus (DMM) surgery was performed in 10-week-old wild type and AMP-activated protein kinase (AMPK)α1 knockout (KO) mice. Metformin (4 mg/day in drinking water) was given, commencing either 2 weeks before or 2 weeks after DMM surgery. Mice were sacrificed 6 and 12 weeks after DMM surgery. OA phenotype was analysed by micro-computerised tomography (μCT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 33 publications
5
144
1
Order By: Relevance
“…A recent study showed the chondroprotective effect of metformin in injury-induced OA animal models [23], which is consistent with our result. OA can have multiple causes, and metformin has a tentative effect when OA has mechanical causes such as meniscus surgery.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A recent study showed the chondroprotective effect of metformin in injury-induced OA animal models [23], which is consistent with our result. OA can have multiple causes, and metformin has a tentative effect when OA has mechanical causes such as meniscus surgery.…”
Section: Discussionsupporting
confidence: 94%
“…The antiarthritic and anti-inflammatory effects of metformin have been reported [12,13]. It has been shown that metformin has a therapeutic effect on OA animal models and cohort studies [14,18,23]. The present study confirmed the therapeutic effect of metformin in rats with MIA-induced OA and, thus, its potential clinical use on OA patients.…”
Section: Discussionsupporting
confidence: 81%
“…4A, Figure S4). Metformin has been shown to promote mitochondrial metabolism via regulation of redox state (33)(34)(35)(36)(37), activation of AMPK (38)(39)(40)(41)(42) and increased the production of lactate (43)(44)(45)(46). Here, metformin was unable to restore intra-tissue lactate or TCA metabolite levels in iMSUD mice unlike in wild type mice, suggesting that BCKDH function is required for metformin action (Fig.…”
Section: Global Dysfunction In Oxidative Carbon Metabolism Caused By mentioning
confidence: 92%
“…Osteoarthritis limited development and delayed progression in a DMM murine model, not in an AMPK/α1 knockout DMM mice [33] Chondroprotection in a partial medial meniscectomy model of non-human primates [33] Reduced knee osteoarthritis progression in obese patients [34] Decreased risk of joint replacement surgery by 25% over 10 years [35] Improvement of osteoarthritis-related pain on a DMM OA mouse model [36] Chondroprotective and antinociceptive effect of intravenous [i.v.] administration of metformin-stimulated Ad-hMSCs [37]…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…Data on this topic are poor and even controversial. However, a very recent investigation [33] demonstrated that metformin administration shortly after joint injury in an OA murine model of destabilization of the medial meniscus (DMM) limited OA development and delayed OA progression, even relieving pain sensitivity. In addition, these benefits were lost in an OA model of AMPK α1 knockout (KO) and DMM mice, thus suggesting that the chondroprotective effect of the drug was mediated by upregulating AMPK α1 expression.…”
Section: Osteoarthritismentioning
confidence: 99%